Revealing Fraud in The Distribution of Cash Direct Assistance - Village Funds - Mahmud Isma'il; Bambang Haryadi; Prasetyono Prasetyono (Universitas Pendidikan Indonesia, 2023)
Main Purpose - The purpose of this study is to reveal fraudulent practices in the distribution of Direct Cash Assistance to Village Funds (BLT-DD) in 2022 for handling Covid-19Method - This study uses a phenomenological approach with data collection methods: observation, interviews, and documentation.Main Findings - The study results show that, first, the mechanism for channeling BLT-DD in cash is used as an opportunity to commit fraud. Second, there is a cut in the BLT-DD money. Third, there is a role conflict in the distribution of BLT-DD, namely, the village head acts as treasurer. Fourth, BPD ignores the oversight function. Fifth, the formation of the BLT-DD volunteer team was only a formality. Sixth, from the deductions from the BLT-DD, village officials and the community who are not on the beneficiary list will also enjoy the deducted money.Theory and Practical Implications - This research is expected to uncover the veil of fraud practices in BLT-DD distribution, providing theoretical, academic, and practical benefits. Revealing facts that occur naturally in the field is an important lesson for readers because what is known so far is in a theoretical context or only on the surface.Novelty - This research contributes significantly and enables new insights into fraudulent practices in BLT-DD distribution.